2022
DOI: 10.3389/ffunb.2022.860777
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Based Diversity Studies and Field Surveys Are Not Mutually Exclusive: On the Importance of Integrated Methodologies in Mycological Research

Abstract: Understanding and describing the diversity of living organisms is a great challenge. Fungi have for a long time been, and unfortunately still are, underestimated when it comes to taxonomic research. The foundations were laid by the first mycologists through field observations. These important fundamental works have been and remain vital reference works. Nevertheless, a non-negligible part of the studied funga escaped their attention. Thanks to modern developments in molecular techniques, the study of fungal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 154 publications
0
10
0
Order By: Relevance
“…The study identified dominant fungi such as Ascomycota, Basidiomycota, and Mucoromycota at the phyla level, though many ASVs were unidentified; this could partly be due to the unavailability of reference sequences in the used UNITE database [57] or possible novelty of the organisms. A report of severe underestimation and underrepresentation of fungal diversity has been previously established [58]. The presence of Ascomycota in all the cultivars may indicate their dominance in the community [29,59], suggesting it to be the core endophytic organism in the plant.…”
Section: Discussionmentioning
confidence: 90%
“…The study identified dominant fungi such as Ascomycota, Basidiomycota, and Mucoromycota at the phyla level, though many ASVs were unidentified; this could partly be due to the unavailability of reference sequences in the used UNITE database [57] or possible novelty of the organisms. A report of severe underestimation and underrepresentation of fungal diversity has been previously established [58]. The presence of Ascomycota in all the cultivars may indicate their dominance in the community [29,59], suggesting it to be the core endophytic organism in the plant.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, certain groups of fungi have few morphological characteristics, and some species may exhibit cryptic diversity or high phenotypic plasticity (e.g., Slepecky and Starmer 2009 ; Haelewaters et al 2018 ; Hapuarachchi et al 2019 ; Van Caenegem et al 2023a ). These observations highlight the need to combine morphological and molecular data whenever possible when dealing with singleton-based species—in line with using integrated methodologies to study fungal diversity (Cazabonne et al 2022 ).…”
Section: Limitations and Risks Of Singleton-based Speciesmentioning
confidence: 89%
“…Similarly, arguments exist for expediting taxonomic processes by employing new approaches such as DNA metabarcoding (Kress & Erickson, 2012) and environmental DNA analysis (Yan et al, 2018). However, these approaches have their own limitations (Cazabonne et al, 2022; de Carvalho et al, 2005). Citizen scientists are often limited in their ability to identify cryptic taxa to species‐level (e.g.…”
Section: Discussionmentioning
confidence: 99%